Problemas de linguagem oral e enurese em crianças: abordagem fonoaudiológica - Birenbaum, Thelma Kilinsky (2010)
Introduction: In addition to oral language disorders, enuresis in children is one of the body marks registered by the listening of speech therapists in clinical practice. Objective: To indentify and analyze the relationships between instances of oral language disorders and enuresis in children. Method: Clinical, quantitative and qualitative, with a descriptive/interpretative outline. Casuistic: 104 children (41 female and 63 male) which attend a philanthropic Institution in Greater São Paulo area, ages ranging from 3;0 to 10;0 years old. Procedure: Stage1: A questionnaire was sent to the children s parents/legal representatives to obtain data on oral language disorders and/or enuresis (daytime and/or night). Step 2: From the responses, there were selected 14 children, all enuretic. Only 10 had complained of oral language disorders. Step 3: Each enuretic child was individually assessed by clinical observation in dialogical situation and application of Behavioral Observation Protocol ( Protocolo de Observação Comportamental-PROC ), item Communicative Abilities (HC) (Zorzi and Hage, 2004). Result interpretation criteria: 1) Quantitative and qualitative analysis of co-occurrences between oral language disorders and enuresis (night and/or daytime) of 104 children was carried out, using descriptive statistics: mean, standard deviation, minimum, median and maximum. Student-t test and Fisher's exact test were used. (Fisher and Van Belle, 1993). 2) An analysis of quantitative and qualitative results in individual evaluation of 14 enuretic children was made. 3) A clinical case study of one of these children, chosen as emblematic of cooccurrence of oral language disorders and enuresis, was performed. The results were discussed and interpreted qualitatively, from the relationship between the clinical material and theoretical references of speech therapy and psychoanalysis. Results and discussion: There are indicators of communication skills impairment on the 14 enuretic children. These showed a higher percentage of oral language disorders comparing to non-enuretic, especially phonological disorders and little talking. These results support the studies on co-occurrence of enuresis and oral language disorders, presented in papers that attach bio-psychic etiology to this comorbidity (Ajuriaguerra, 1980; Font, 1985, 1987; Dolto and Hamad, 1998; Dolto, 1999, 2007). Conclusion: Results indicated relationship between enuresis and oral language disorders. Considering the interactions among language, body and psyche, it is suggested that speech therapists, when dealing with oral language disorders in children, also investigate the acquisition of their bladder sphincter control, in a biopsychical approach